用于混合电动车辆的控制设备 (2016)
种用于混合电动车辆的控制设备，包括：配置成检测电池温度的温度检测器；配置成根据检测到的电池温度计算温度上升速度也就是单位时间内的温度上升量的温度上升速度计算器；以及配置成在温度上升速度等于或者高于阈值时使得发动机启动，以使发电机产生电能的发动机控制器。阈值被设定成使得检测到的电池温度越高，阈值越低。 A control apparatus for a hybrid electric vehicle, includes: a temperature detector configured to detect a temperature of the battery; a temperature increase rate calculator configured to calculate, based on the detected temperature of the battery, a temperature increase rate that is an amount of increase in the temperature per unit time; and an engine controller configured to allow, when the temperature increase rate is equal to or higher than a threshold value, the engine to be started, so that the generator generates the electric power. The threshold value is set so that the higher the detected battery temperature, the lower the threshold value.